Biohybrid 3D Printing of a Tissue‐Sensor Platform for Wireless, Real‐Time, and Continuous Monitoring of Drug‐Induced Cardiotoxicity (Adv. Mater. 11/2023). Issue 11 (16th March 2023) - Yong, Uijung; Kim, Donghwan; Kim, Hojoong; Hwang, Dong Gyu; Cho, Sungkeon; Nam, Hyoryung; Kim, Sejin; Kim, Taeyeong; Jeong, Unyong; Kim, Keehoon; Chung, Wan Kyun; Yeo, Woon‐Hong; et al.
Abstract : Tissue–Sensor Platforms In article number 2208983, Uijung Yong, Donghwan Kim, Hojoong Kim, Woon‐Hong Yeo, Jinah Jang, and co‐workers report a biohybrid 3D‐printing method for the fabrication of tissue–sensor platforms. The integration of electronics with living cardiac tissues makes it possible to continuously monitor their contractile force and, ultimately, of the drug‐induced cardiotoxicity effects on cardiac tissues. This method can create a next‐generation tissue–sensor platform for an effective drug development process.